THE MARGINALISATION OF WATER POLITICS IN MALAYSIA’S POLITICAL DISCOURSE - Abdullah, Mohd Firdaus; Mohd Noor, Arba’iyah; Abdul Majid , Marina; Shahidan, Shaiful (SARJANA, 2025)
ABSTRACT This article argues that the persistent sidelining of water in Malaysia’s political discourse is not accidental mismanagement but a systemic project of depoliticisation that protects entrenched interests. Combining a critical reading of federal and state law and policy, longitudinal analysis of party manifestos and discourse analysis of political debates and mainstream media, it shows how a technocratic lexicon such as “capacity,” “leakages,” “NRW,” and “mitigation works” strips water of rights-based claims and relocates it to the domain of engineering. The article extends the hydro-hegemony framework to the domestic arena, demonstrating how elite narrative control, concessionary regimes, and opaque bureaucracies reproduce postcolonial hierarchies while rendering affected communities data points rather than political subjects. It identifies “water populism” as a distinctive affective politics in which state elites mobilise territorial grievance, for example interstate river disputes, to deflect accountability without instituting structural reform. Failures of federalism, including legal ambiguities, fiscal asymmetries, and the absence of inter-state conflict resolution, compound these dynamics, while education, religion, and media normalise crisis and mute collective anger, amounting to sovereign neglect. The article contributes a normative and institutional agenda for hydro-democracy in Malaysia: recognising water as a political right, legislating a rights anchored National Water Act, mandating transparency over concessions and performance data, and institutionalising participatory governance across planning, tariff setting, and oversight. It concludes that without reclaiming water from technocracy and populism, Malaysia’s democracy remains hollowed out at its most elemental threshold, namely the guarantee of dignified and equitable access to clean water.